2013
DOI: 10.3390/ijms14022370
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 Expression in Brain Metastases from Colorectal Cancer and Corresponding Primary Tumors: A Case Cohort Series

Abstract: Brain metastases (BM) from colorectal cancer (CRC) are a rare but increasing event. Surgical resection of oligometastatic disease, including BM, may produce a survival benefit in selected patients. Previous studies described the HER-2 expression patterns in CRC patients, but its prognostic role still remains controversial. Information on the HER-2 expression in BM from CRC is currently lacking. Among the over 500 patients treated at our Department of Neurosurgery in the last 13 years (1999–2012), we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 58 publications
(70 reference statements)
2
16
0
Order By: Relevance
“…As demonstrated in our preliminary studies [ 23 ], high HER-2 expression was found mainly in primary tumors in rectal cancer patients ( n = 4; 18.2%). The rate of HER-2 positivity in metastases was 8% analogous to findings from Aprile et al[ 28 ] ( n = 50) with HER-2 overexpression in 12% of brain metastases. Furthermore, similarly high levels of concordance were reported for metastases and corresponding primary tumors in CRC patients [ 28 ][ 46 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As demonstrated in our preliminary studies [ 23 ], high HER-2 expression was found mainly in primary tumors in rectal cancer patients ( n = 4; 18.2%). The rate of HER-2 positivity in metastases was 8% analogous to findings from Aprile et al[ 28 ] ( n = 50) with HER-2 overexpression in 12% of brain metastases. Furthermore, similarly high levels of concordance were reported for metastases and corresponding primary tumors in CRC patients [ 28 ][ 46 ].…”
Section: Discussionsupporting
confidence: 85%
“…HER-2 dimerizes preferentially with the HER-3 receptor initiating potential signal transduction leading to cell proliferation, angiogenesis and formation of metastases [ 33 ]. Several studies have reported varying expression levels of HER-2 and HER-3 and evaluated their correlation with clinico-pathological parameters and prognosis but with divergent results [ 23 ][ 28 ][ 29 ][ 34 ][ 35 ]. Still, in a variety of solid tumors, the HER-2 receptor represents an effective target for monoclonal antibodies such as trastuzumab being approved for metastatic gastric cancer, pertuzumab [ 36 ] or antibody-drug-conjugates such as T-DM-1 [ 37 ] and for small tyrosine kinase inhibitors like lapatinib [ 38 ] and afatinib [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Activation of HER-2/neu, activates the pathways that play a primary role in cell proliferation and cell differentiation. Recent studies reported that deregulated HER-2 expression/activity is pivotal in oncogenic transformation, tumorigenesis, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…9 Previous studies showed overexpression of HER-2 in wide range of 0-84% among patients with CRC. 8-10 …”
Section: Introductionmentioning
confidence: 99%